Cycloaddition catalyst, preparation method and application thereof, and method for preparing cyclic carbonate by cycloaddition of CO2 and epoxide
By using a catalyst with domain-limited nanocage material, the problem of poor catalytic performance of traditional catalysts in the cycloaddition reaction of CO2 and epoxide is solved, high activity and good cyclic performance are achieved, and the efficient preparation of cyclic carbonate is promoted.
Patent Information
- Application Number
- CN202111249869.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-10-26
AI Technical Summary
The traditional metal Schiff base complex-based catalyst has problems such as unsatisfactory catalytic performance, difficulty in recycling and difficulty in product purification in the preparation of cyclic carbonate with epoxide cycloaddition, which seriously restricts its industrial application.
A catalyst prepared by combining nanocage material CS, active center M (Salen)X1X2 and co-active center ZR*4Y is used to improve catalytic activity and cyclic performance through the nanocage structure's domain-limited active center.
The high activity of the catalyst and good recycling performance were achieved, especially in the reaction of CO2 and epoxide cycloaddition to prepare cyclic carbonate.
Smart Images

Figure CN116020568B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cyclic carbonate preparation, and specifically relates to a cycloaddition catalyst and a preparation method and application thereof, and a method for preparing cyclic carbonate by cycloaddition of CO2 and epoxide. Background Art
[0002] The preparation of cyclic carbonates by cycloaddition of CO2 and epoxides has important practical significance. This is mainly because, on the one hand, it realizes the conversion of CO2 into chemicals; on the other hand, the obtained product, cyclic carbonate, is a widely used chemical raw material, which can be used as an intermediate for fine chemical synthesis, aprotic polar solvent, electrolyte for lithium-ion batteries, monomer for polymerization reaction, and intermediate for many chemical substances and drugs.
[0003] To date, a variety of catalysts have been developed, such as homogeneous alkali metal halides (ChemSusChem, 2012, 5, 652), ionic liquids (RSC Adv., 2014, 4, 2360), metal Schiff base complexes (Chem. Commun., 2010, 46, 4580), metal porphyrin complexes (Angew. Chem. Int. Ed., 2015, 54, 134) and heterogeneous ionic liquid porous polymers (Chem. Asian J., 2017, 12, 557), ion exchange resins (Green Chem., 2005, 7, 518) and metal organic framework complexes (J. Am. Chem. Soc., 2014, 136, 15861.). Among them, metal Schiff base complex is a kind of catalyst that can efficiently catalyze CO2 and epoxide cycloaddition to prepare cyclic carbonate reaction (J.Org.Chem.2003,68,1559), but it is homogeneous, and there are problems such as catalyst cannot be recycled and product purification is difficult. Although there are also methods by immobilization and polymerization to make it a heterogeneous catalyst, the performance is still to be improved, which seriously restricts its industrial application. Therefore, this area is in an urgent need to develop a metal Schiff base complex-based heterogeneous catalyst that can efficiently catalyze CO2 and epoxide cycloaddition to prepare cyclic carbonate reaction. Summary of the invention
[0004] Aiming at the defect that the catalytic performance of the conventional cycloaddition catalyst is not ideal, the present invention provides a cycloaddition catalyst with high catalytic activity and good cycle performance, and a preparation method and application thereof.
[0005] In a first aspect, the present invention provides a cycloaddition catalyst comprising:
[0006] Nanocage material CS, active center M(Salen)X 1 X 2and the co-active center ZR*4Y;
[0007] Among them, the active center M(Salen)X 1 X 2 In the formula, M is a metal ion, Salen is a Shiff base derivative, and X 1 , X 2 is an axial anion; depending on the valence state of the M metal, it may optionally contain X 1 and / or X 2 ;
[0008] Among them, in the co-active center ZR*4Y, Z is nitrogen and / or phosphorus, R* is an aliphatic or aromatic carbon chain, and Y is a halogen anion;
[0009] Wherein, the nanocage material CS is a mesoporous silica-based material containing carbon deposits and having a nanocage structure.
[0010] In a second aspect, the present invention provides a method for preparing the catalyst, wherein the method comprises: 1 X 2 , the co-active center ZR*4Y, and the nanocage material CS are contacted with a solvent, and the solvent is removed; an encapsulation agent is added for encapsulation; then the mixture of water and alcohol is treated, and then washed with alcohol, and then dried.
[0011] In a third aspect, the present invention provides an application of the cycloaddition catalyst in the preparation of cyclic carbonates by cycloaddition of CO2 and epoxide.
[0012] In a fourth aspect, the present invention provides a method for preparing cyclic carbonate by cycloaddition of CO2 and epoxide, the method comprising contacting epoxide with CO2 in the presence of a cycloaddition catalyst, wherein the cycloaddition catalyst is the aforementioned catalyst, and the contact conditions include: pressure of 0.5-5MPa, temperature of 20-120°C, and time of 2-24 hours.
[0013] By adopting the above technical solution, the present invention has the following technical advantages:
[0014] The catalyst of the present invention comprises a base material containing a nano cage structure and an active center M(Salen)X confined in the nano cage. 1 X 2 and the co-active center ZR*4Y, which have high activity and good recycling performance for cycloaddition reactions, especially for the cycloaddition of CO2 and epoxides to prepare cyclic carbonates.
[0015] According to the preparation method of the catalyst of the present invention, the activity and recycling performance of the catalyst can be further improved. The preparation method provided by the present invention is simple and feasible, and can provide a reference for the synthesis of other nanocage confined catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a TEM photograph of catalyst A prepared in Example 1. DETAILED DESCRIPTION
[0017] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0018] The present invention provides a cycloaddition catalyst, which contains:
[0019] Nanocage material CS, active center M(Salen)X 1 X 2 and the co-active center ZR*4Y;
[0020] Among them, the active center M(Salen)X 1 X 2 In the formula, M is a metal ion, Salen is a Shiff base derivative, and X 1 , X 2 is an axial anion; depending on the valence state of the M metal, it may optionally contain X 1 and / or X 2 ;
[0021] Among them, in the co-active center ZR*4Y, Z is nitrogen and / or phosphorus, R* is an aliphatic or aromatic carbon chain, and Y is a halogen anion;
[0022] Wherein, the nanocage material CS is a mesoporous silica-based material containing carbon deposits and having a nanocage structure.
[0023] The catalyst of the present invention comprises a base material containing a nano cage structure and an active center M(Salen)X confined in the nano cage. 1 X 2 and the co-active center ZR*4Y, which has high activity for cycloaddition reactions and good recycling performance.
[0024] In the present invention, as long as the purpose of the present invention can be achieved, there is no special requirement for the content of carbon deposits in the nano cage material CS. According to a preferred embodiment of the present invention, the content of carbon deposits is 0.5-5.5% by weight based on the total weight of the nano cage material CS. By adopting the above preferred scheme, the activity and cycle performance of the cycloaddition catalyst can be further improved. In the present invention, carbon deposits are carbonized surfactants, which may also contain hydrogen and oxygen. The carbon deposit content is measured by thermogravimetry.
[0025] In the present invention, the mesoporous silica-based material can be a conventional choice in the art. According to a preferred embodiment of the present invention, the mesoporous silica-based material is selected from one or more of SBA-6, SBA-16, FDU-1, FDU-12, KIT-5 and AMS-8. By adopting the above preferred embodiment, the activity and cycle performance of the cycloaddition catalyst can be further improved.
[0026] In the present invention, there is no special requirement for the preparation method of the nanocage material CS. For example, the nanocage material CS can be obtained by a sol-gel method combined with an inert atmosphere heat treatment.
[0027] In order to further improve the activity and cycle performance of the cycloaddition catalyst, according to a preferred embodiment of the present invention, the preparation method of the nanocage material CS comprises: obtaining a solid mesoporous silica-based material containing a surfactant according to a sol-gel method, and heat-treating the solid mesoporous silica-based material in an inert atmosphere, or first in an inert atmosphere and then in an oxygen-containing atmosphere.
[0028] In the present invention, the conditions for the heat treatment can be selected according to conventional techniques in the art. According to a preferred embodiment of the present invention, the conditions for the heat treatment include: a temperature of 300-1000°C, preferably 400-700°C; a time of more than 0.5h, preferably 2-6h. By adopting the above preferred scheme, the activity and cycle performance of the cycloaddition catalyst can be further improved.
[0029] According to a preferred embodiment of the present invention, the oxygen-containing atmosphere may be any atmosphere containing oxygen, such as air.
[0030] According to a preferred embodiment of the present invention, the preferred heat treatment conditions include: treatment at 300-500° C. in an inert atmosphere for 0.5-4 h; treatment at 500-700° C. in an air atmosphere for 1-6 h.
[0031] According to a preferred embodiment of the present invention, the inert atmosphere can be various inert atmospheres, preferably nitrogen and / or helium atmosphere. By adopting the above preferred embodiment, the activity and cycle performance of the cycloaddition catalyst can be further improved.
[0032] In the present invention, as long as the purpose of the present invention can be achieved, the nano cage material CS, the active center M (Salen) X 1 X 2 There is no special requirement for the mass ratio of the co-active center ZR*4Y. According to a preferred embodiment of the present invention, the mass of the nanocage material CS is equal to that of the active center M(Salen)X 1 X 2 The total mass ratio of the co-active center ZR*4Y is (10-100): 1, preferably (10-25): 1. By adopting the above preferred embodiment, the activity and cycle performance of the cycloaddition catalyst can be further improved.
[0033] According to a preferred embodiment of the present invention, the active center M(Salen)X 1 X 2 The molar ratio of the co-active center ZR*4Y is 1:(0.5-3), preferably 1:(0.5-2). By adopting the above preferred embodiment, the activity and cycle performance of the cycloaddition catalyst can be further improved.
[0034] In order to further improve the activity and cycle performance of the cycloaddition catalyst, according to a preferred embodiment of the present invention, in the co-active center ZR*4Y, the R* is a butyl group or a phenyl group.
[0035] According to a preferred embodiment of the present invention, the active center M(Salen)X 1 X 2 , having a structure shown in the following formula (I):
[0036]
[0037] Wherein: in formula (I) The structure is selected from one or more of the following structures:
[0038]
[0039] In order to further improve the activity and cycle performance of the cycloaddition catalyst, according to a preferred embodiment of the present invention, R 1 , R 2 At least one selected from tert-butyl, methoxy, H, nitro, phenyl, Cl, Br, preferably at least one selected from tert-butyl, H.
[0040] In order to further improve the activity and cycle performance of the cycloaddition catalyst, according to a preferred embodiment of the present invention, when M is a tetravalent metal, preferably M is Sn, X 1 , X 2 Selected from Cl - ,Br - , I- ,OAc - , OTs - , OTf - , NO3 - , ClO4 - , Cl3CCO2 - , F3CCO2 - , BF4 - , PF6 - , at least one of p-NO2-C6H4CO2, preferably Cl - ,OAc - , OTs - , Cl3CCO2 - , F3CCO2 - At least one of .
[0041] In order to further improve the activity and cycle performance of the cycloaddition catalyst, according to a preferred embodiment of the present invention, when M is a trivalent metal, preferably M is selected from Al, Co, Mn, Ru or Ir, the active center M(Salen)X 1 X 2 Medium X 1 and X 2 Only one is kept, selected from Cl - ,Br - , I - ,OAc - , OTs - , OTf - , NO3 - , ClO4 - , Cl3CCO2 - , F3CCO2 - , BF4 - , PF6 - , at least one of p-NO2-C6H4CO2, preferably selected from Cl - ,OAc - , OTs - , Cl3CCO2 - , F3CCO2 - At least one of .
[0042] In order to further improve the activity and cycle performance of the cycloaddition catalyst, according to a preferred embodiment of the present invention, when M is a divalent metal, preferably selected from Zn, Sn, Cu or Co, and there is no X 1 and X 2 .
[0043] According to a preferred embodiment of the present invention, the active center M(Salen)X 1 X 2One or more selected from Co(N,N′-disalicylidene-1,2-cyclohexanediamine)OAc, Co(N,N′-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediamine)OTs, Co(N,N′-disalicylidene-1,2-cyclohexanediamine)Cl3CCO2, Sn(N,N′-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediamine)Cl2, Zn(N,N′-disalicylidene-1,2-cyclohexanediamine), Al(N,N′-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediamine)Cl;
[0044] According to a preferred embodiment of the present invention, the co-active center ZR*4Y is selected from one or more of tetraphenylphosphonium bromide, tetrabutylammonium chloride and tetrabutylammonium bromide.
[0045] The present invention provides a method for preparing the catalyst, wherein the method comprises: 1 X 2 , the co-active center ZR*4Y, and the nanocage material CS are contacted with a solvent, and the solvent is removed; an encapsulation agent is added for encapsulation; then the mixture of water and alcohol is treated, and then washed with alcohol, and then dried.
[0046] According to the preparation method of the catalyst of the present invention, the activity and recycling performance of the catalyst can be further improved. The preparation method provided by the present invention is simple and feasible, and can provide a reference for the synthesis of other nanocage confined catalysts.
[0047] According to a preferred embodiment of the present invention, the preparation method of the nanocage material CS comprises: obtaining a solid mesoporous silica-based material containing a surfactant according to a sol-gel method, and heat-treating the solid mesoporous silica-based material in an inert atmosphere, or first in an inert atmosphere and then in an oxygen-containing atmosphere. By adopting the above preferred scheme, the activity and cycle performance of the cycloaddition catalyst can be further improved.
[0048] In order to further improve the activity and cycle performance of the cycloaddition catalyst, according to a preferred embodiment of the present invention, the heat treatment conditions include: temperature of 300-1000°C, preferably 400-700°C; time of more than 0.5h, preferably 2-6h.
[0049] According to a preferred embodiment of the present invention, the oxygen-containing atmosphere may be any atmosphere containing oxygen, such as air.
[0050] According to a preferred embodiment of the present invention, the preferred heat treatment conditions include: treatment at 300-500° C. in an inert atmosphere for 0.5-4 h; treatment at 500-700° C. in an air atmosphere for 1-6 h.
[0051] In order to further improve the activity and cycle performance of the cycloaddition catalyst, according to a preferred embodiment of the present invention, the inert atmosphere is a nitrogen and / or helium atmosphere.
[0052] In order to further improve the activity and cycle performance of the cycloaddition catalyst, according to a preferred embodiment of the present invention, the mesoporous silica-based material is selected from one or more of SBA-6, SBA-16, FDU-1, FDU-12, KIT-5 and AMS-8.
[0053] In the present invention, preferably the contacting conditions include: dynamic mixing at room temperature for 0.5-5h.
[0054] In the present invention, as long as the purpose of the present invention can be achieved, the solvent can be a conventional choice in the art. According to a preferred embodiment of the present invention, the solvent includes ethanol and / or methanol. By adopting the above preferred embodiment, the activity and cycle performance of the cycloaddition catalyst can be further improved.
[0055] In the present invention, as long as the purpose of the present invention can be achieved, the temperature for removing the solvent can be a conventional choice in the art. According to a preferred embodiment of the present invention, the temperature for removing the solvent is -96°C to 61°C, preferably 20 to 40°C. By adopting the above preferred embodiment, the activity and cycle performance of the cycloaddition catalyst can be further improved.
[0056] According to a preferred embodiment of the present invention, in the mixture of water and alcohol, the alcohol is selected from ethanol and / or methanol. By adopting the above preferred embodiment, the activity and cycle performance of the cycloaddition catalyst can be further improved.
[0057] According to a preferred embodiment of the present invention, in the mixture of water and alcohol, the volume percentage of water is 1% to 50%, preferably 2% to 25%, preferably 3% to 7%. By adopting the above preferred scheme, the activity and cycle performance of the cycloaddition catalyst can be further improved.
[0058] According to a preferred embodiment of the present invention, the alcohol used for washing includes ethanol and / or methanol.
[0059] In the present invention, as long as the purpose of the present invention can be achieved, the encapsulating agent can be a conventional choice in the art. According to a preferred embodiment of the present invention, the encapsulating agent is a silane coupling agent, preferably a silane coupling agent selected from one or more of methyl orthosilicate, propyltrimethoxysilane, hexamethyldisilazane and chlorotrimethylsilane. For example, 7.304g of methyl orthosilicate and 3.456g of water are stirred at 25°C until clear for pre-hydrolysis.
[0060] The present invention provides an application of the cycloaddition catalyst in preparing cyclic carbonate by cycloaddition of CO2 and epoxide.
[0061] The present invention provides a method for preparing cyclic carbonate by cycloaddition of CO2 and epoxide. The method comprises contacting epoxide with CO2 in the presence of a cycloaddition catalyst, wherein the cycloaddition catalyst is the aforementioned catalyst, and the contact conditions comprise: a pressure of 0.5-5MPa, a temperature of 20-120°C, and a time of 2-24 hours.
[0062] According to the method for preparing cyclic carbonates by cycloaddition of CO2 and epoxide provided by the present invention, high value-added cyclic carbonates such as ethylene carbonate and propylene carbonate can be prepared.
[0063] The present invention is further described below by specific examples, and the scope of the present invention is not limited to the scope covered by the examples. The catalyst activity is calculated as the cyclic carbonate yield, and the specific calculation method is as follows:
[0064] Cyclic carbonate yield = actually obtained cyclic carbonate mass * 100% / theoretically obtained cyclic carbonate mass.
[0065] Example 1
[0066] Weigh 0.50 g of F127, 0.6 g of mesitylene and 2.5 g of KCl, dissolve them in 30 mL of 2M HCl aqueous solution at 16°C, and stir for 2 h; add 2.08 g of TEOS, continue stirring at 16°C for 24 h, and then place in a 100°C oven for hydrothermal treatment for 24 h.
[0067] After being taken out, washed and dried, the nanocage material CS-FDU-12 containing 5.5% carbon deposits was obtained by treating it at 500°C for 4 h in a nitrogen atmosphere.
[0068] Weigh 3.0g of FDU-12 containing 5.5% carbon deposits, place in 6mL of ethanol solution containing 43.3mg of Co(N,N′-disalicylidene-1,2-cyclohexanediamine)OAc and 83.8mg of tetraphenylphosphonium bromide, stir at 25℃ for 2h, then stir at 40℃ until the solvent evaporates. Add pre-hydrolyzed methyl orthosilicate (7.304g of methyl orthosilicate and 3.456g of water are stirred at 25℃ until clear), stir for 20min, then add a mixture of water and ethanol with a volume percentage of 5%, stir evenly, centrifuge, wash thoroughly with ethanol, and dry to obtain catalyst A. Figure 1 is the TEM image of catalyst A. Figure 1 It can be seen that catalyst A presents a nanocage structure.
[0069] Example 2
[0070] Weigh 0.50 g of F127, 0.6 g of mesitylene and 2.5 g of KCl, dissolve them in 30 mL of 2M HCl aqueous solution at 16°C, and stir for 2 h; add 2.08 g of TEOS, continue stirring at 16°C for 24 h, and then place in a 100°C oven for hydrothermal treatment for 24 h.
[0071] After washing and drying, the nanocage material CS-FDU-12 containing 3.5% carbon deposits was obtained by treating it at 400°C for 2 h in a nitrogen atmosphere and then at 600°C for 2 h in an air atmosphere.
[0072] Weigh 2.0g of FDU-12 containing 3.5% carbon deposits, place in 6mL of methanol solution containing 66.2mg Co(N,N′-bis(3,5-di-tert-butyl salicylidene)-1,2-ethylenediamine)OTs and 64.4mg tetrabutylammonium bromide, stir at 25℃ for 2h, then stir at 40℃ until the solvent evaporates. Add pre-hydrolyzed methyl orthosilicate (7.304g of methyl orthosilicate and 3.456g of water are stirred at 25℃ until clear), stir for 20min, then add a mixture of water and methanol with a volume percentage of 3%, stir evenly and centrifuge, repeat once, then wash thoroughly with ethanol and dry to obtain catalyst B.
[0073] Example 3
[0074] Weigh 0.50 g of F127, 0.6 g of mesitylene and 2.5 g of KCl, dissolve them in 30 mL of 2M HCl aqueous solution at 16°C, and stir for 2 h; add 2.08 g of TEOS, continue stirring at 16°C for 24 h, and then place in a 100°C oven for hydrothermal treatment for 24 h.
[0075] After being taken out, washed and dried, the nanocage material CS-FDU-12 containing 0.5% carbon deposits was obtained by treating it at 400°C for 0.5 h in a helium atmosphere and then at 600°C for 5.5 h in an air atmosphere.
[0076] Weigh 2.0g of FDU-12 containing 0.5% carbon deposits, place in 6mL of ethanol solution containing 48.5mg Co(N,N′-disalicylidene-1,2-ethylenediamine)Cl3CCO2 and 64.4mg tetrabutylammonium bromide, stir at 25℃ for 2h, then stir at 40℃ until the solvent evaporates. Add pre-hydrolyzed methyl orthosilicate (stir 7.304g of methyl orthosilicate and 3.456g of water at 25℃ until clear), stir for 40min, then add a mixture of water and methanol with a volume percentage of 7%, stir evenly, centrifuge, wash thoroughly with methanol, and dry to obtain catalyst C.
[0077] Example 4
[0078] 2.0 g of FDU-12 containing 3.5% carbon deposits (prepared as in Example 2) was weighed and placed in 6 mL of methanol solution containing 55.4 mg of Al(N,N′-bis(3,5-di-tert-butyl salicylidene)-1,2-ethylenediamine)Cl and 55.4 mg of tetrabutylammonium chloride. After being sealed and stirred at 25°C for 2 hours, it was stirred open at 40°C until the solvent evaporated. Pre-hydrolyzed methyl orthosilicate (7.304 g of methyl orthosilicate and 3.456 g of water were stirred at 25°C until clear) was added at 25°C. After stirring for 20 minutes, a mixture of water and methanol with a volume percentage of 3% was added. After stirring evenly, the mixture was centrifuged and separated. The mixture was repeated once, and then the mixture was fully washed with ethanol and dried to obtain catalyst D.
[0079] Example 5
[0080] Weigh 2.0 g of F108 and 5.24 g of K2SO4 and dissolve them in 60 g of 2M HCl aqueous solution at 35°C, and stir for 2 h; add 4.25 g of TEOS, continue stirring at 35°C for 24 h, and then place in a 100°C oven for hydrothermal treatment for 48 h.
[0081] After washing and drying, the nanocage material CS-SBA-16 containing 3.5% carbon deposits was obtained by treating it at 400°C for 2 h in a nitrogen atmosphere and then at 600°C for 2 h in an air atmosphere.
[0082] Weigh 1.5g of SBA-16 containing 3.5% carbon deposits, place in 6mL of methanol solution containing 68.1mg Sn(N,N′-bis(3,5-di-tert-butyl salicylidene)-1,2-ethylenediamine)Cl2 and 55.4mg tetrabutylammonium chloride, stir at 25℃ for 2h, then stir at 40℃ until the solvent evaporates. Add pre-hydrolyzed methyl orthosilicate (7.304g of methyl orthosilicate and 3.456g of water are stirred at 25℃ until clear), stir for 20min, then add a mixture of water and methanol with a volume percentage of 3%, stir evenly and centrifuge, repeat once, then wash thoroughly with ethanol and dry to obtain catalyst E.
[0083] Example 6
[0084] Weigh 0.5 g of F127 and dissolve it in 24 mL of deionized water and 1.05 g of 35% hydrochloric acid solution. Add 2.40 g of TEOS under vigorous stirring at 45°C, continue stirring at 45°C for 24 hours, and then place in a 100°C oven for hydrothermal heating for 24 hours.
[0085] After washing and drying, the nanocage material CS-KIT-5 containing 3.5% carbon deposits was obtained by treating it at 400°C for 2 h in a nitrogen atmosphere and then at 600°C for 2 h in an air atmosphere.
[0086] Weigh 2.0g of KIT-5 containing 3.5% carbon deposits, place in 6mL of methanol solution containing 38.1mg Zn(N,N′-disalicylidene-1,2-cyclohexanediamine) and 55.4mg tetrabutylammonium chloride, stir at 25℃ for 2h, then stir at 40℃ until the solvent evaporates. Add pre-hydrolyzed methyl orthosilicate (7.304g of methyl orthosilicate and 3.456g of water are stirred at 25℃ until clear), stir for 20min, then add a mixture of water and methanol with a volume percentage of 3%, stir evenly and centrifuge, repeat once, then wash thoroughly with ethanol and dry to obtain catalyst F.
[0087] Comparative Example 1
[0088] Weigh 0.50 g of F127, 0.6 g of mesitylene and 2.5 g of KCl, dissolve them in 30 mL of 2M HCl aqueous solution at 16°C, and stir for 2 h; add 2.08 g of TEOS, continue stirring at 16°C for 24 h, and then place in a 100°C oven for hydrothermal treatment for 24 h.
[0089] After being taken out, washed and dried, the product was treated at 550°C for 6 hours in an air atmosphere to obtain FDU-12 free of carbon deposits.
[0090] Weigh 2.0g of FDU-12 without carbon deposits, place it in 6mL of methanol solution containing 55.4mg Al(N,N′-bis(3,5-di-tert-butyl salicylidene)-1,2-ethylenediamine)Cl and 55.4mg tetrabutylammonium chloride, stir at 25℃ for 2h, then stir at 40℃ until the solvent evaporates. Add pre-hydrolyzed methyl orthosilicate (7.304g of methyl orthosilicate and 3.456g of water are stirred at 25℃ until clear), stir for 20min, then add a mixture of water and methanol with a volume percentage of 3%, stir evenly and centrifuge, repeat once, then wash thoroughly with ethanol and dry to obtain catalyst G.
[0091] Embodiment 7-48
[0092] In an intermittent reactor, 100 mmol of PO and 0.1 mmol of nanocage catalyst AG containing active centers were added, CO2 was introduced to make the pressure 1 MPa, the reaction time was 10 h, and the activity of each catalyst was investigated at temperatures of 20, 40, 60, 80, 100, and 120 °C, as shown in Table 1.
[0093] Table 1 Yield of cyclic carbonate obtained by catalyst AG / %
[0094] Temperature / ℃ A B C D E F G 20 ≥86 ≥87 ≥87 ≥88 ≥86 ≥86 ≥83 40 ≥90 ≥91 ≥91 ≥92 ≥90 ≥90 ≥87 60 ≥93 ≥94 ≥94 ≥95 ≥93 ≥93 ≥90 80 ≥96 ≥97 ≥97 ≥98 ≥96 ≥96 ≥93 100 ≥99 ≥99 ≥99 ≥99 ≥99 ≥99 ≥96 120 ≥99 ≥99 ≥99 ≥99 ≥99 ≥99 ≥97
[0095] It can be seen from the data in the above table that all catalysts have high activity, and the activity is higher when containing a small amount of carbon deposits, and high temperature is more conducive to the reaction.
[0096] Examples 49-54
[0097] In an intermittent reactor, 100 mmol of PO and 0.1 mmol of nanocage catalyst D containing active centers were added, CO2 was introduced to a pressure of 1 MPa, the reaction time was 10 h, and the temperature was 100°C. The recyclability of catalyst D was investigated, as shown in Table 2.
[0098] Table 2 Yield of cyclic carbonate obtained during the recycling of catalyst D / %
[0099]
[0100] Comparative Example 2
[0101] In an intermittent reactor, add 100 mmol of PO, 0.1 mmol of Al(N,N′-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediamine)Cl, 0.2 mmol of tetrabutylammonium chloride, introduce CO2 to make the pressure 1 MPa, the temperature is 100°C, react for 10 hours, and the yield of cyclic carbonate is 90%.
[0102] From the data of Comparative Example 2 and the data of the embodiments of the present invention, it can be seen that the nanocage catalyst obtained by confining the active center and the co-active center in the nanocage has a higher activity.
[0103] Comparative Examples 3-8
[0104] In an intermittent reactor, 100 mmol of PO and 0.1 mmol of nanocage catalyst G containing active centers were added, CO2 was introduced to a pressure of 1 MPa, the reaction time was 10 h, and the temperature was 100°C. The recyclability of catalyst G was investigated, as shown in Table 3.
[0105] Table 3 Yield of cyclic carbonate obtained during the recycling of catalyst G / %
[0106]
[0107] From the data of comparative examples 3-8 and the data of the embodiments of the present invention, it can be seen that the nanocage material contains a small amount of carbon deposits, which can improve the recyclability of the catalyst.
[0108] Embodiment 55
[0109] Weigh 0.50 g of F127, 0.6 g of mesitylene and 2.5 g of KCl, dissolve them in 30 mL of 2M HCl aqueous solution at 16°C, and stir for 2 h; add 2.08 g of TEOS, continue stirring at 16°C for 24 h, and then place in a 100°C oven for hydrothermal treatment for 24 h.
[0110] After being taken out, washed and dried, the nanocage material CS-FDU-12 containing 7.5% carbon deposits was obtained by treating it at 300°C for 24 hours in a nitrogen atmosphere.
[0111] Weigh 2.0g of FDU-12 containing 7.5% carbon deposits, place in 6mL of methanol solution containing 55.4mg Al(N,N′-bis(3,5-di-tert-butyl salicylidene)-1,2-ethylenediamine)Cl and 55.4mg tetrabutylammonium chloride, stir at 25℃ for 2h, then stir at 40℃ until the solvent evaporates. Add pre-hydrolyzed methyl orthosilicate (7.304g of methyl orthosilicate and 3.456g of water are stirred at 25℃ until clear), stir for 20min, then add a mixture of water and methanol with a volume percentage of 3%, stir evenly and centrifuge, repeat once, then wash thoroughly with ethanol and dry to obtain catalyst H.
[0112] Embodiment 56
[0113] Weigh 0.50 g of F127, 0.6 g of mesitylene and 2.5 g of KCl, dissolve them in 30 mL of 2M HCl aqueous solution at 16°C, and stir for 2 h; add 2.08 g of TEOS, continue stirring at 16°C for 24 h, and then place in a 100°C oven for hydrothermal treatment for 24 h.
[0114] After washing and drying, the nanocage material CS-FDU-12 containing 3.5% carbon deposits was obtained by treating it at 400°C for 2 h in a nitrogen atmosphere and then at 600°C for 2 h in an air atmosphere.
[0115] Weigh 2.0 g of FDU-12 containing 3.5% carbon deposits, place in 6 mL of methanol solution containing 57.9 mg of Cr(N,N′-bis(3,5-di-tert-butyl salicylidene)-1,2-ethylenediamine)Cl and 55.4 mg of tetrabutylammonium chloride, stir at 25°C for 2 h, then stir at 40°C until the solvent evaporates. Add pre-hydrolyzed methyl orthosilicate (7.304 g of methyl orthosilicate and 3.456 g of water are stirred at 25°C until clear), stir for 20 min, then add a mixture of water and methanol with a volume percentage of 3%, stir evenly and centrifuge, repeat once, then wash thoroughly with ethanol and dry to obtain catalyst I.
[0116] Embodiment 57
[0117] Weigh 0.50 g of F127, 0.6 g of mesitylene and 2.5 g of KCl, dissolve them in 30 mL of 2M HCl aqueous solution at 16°C, and stir for 2 h; add 2.08 g of TEOS, continue stirring at 16°C for 24 h, and then place in a 100°C oven for hydrothermal treatment for 24 h.
[0118] After washing and drying, the nanocage material CS-FDU-12 containing 3.5% carbon deposits was obtained by treating it at 400°C for 2 h in a nitrogen atmosphere and then at 600°C for 2 h in an air atmosphere.
[0119] Weigh 1.0g of FDU-12 containing 3.5% carbon deposits, place in 6mL of methanol solution containing 55.4mg Al(N,N′-bis(3,5-di-tert-butyl salicylidene)-1,2-ethylenediamine)Cl and 55.4mg tetrabutylammonium chloride, stir at 25℃ for 2h, then stir at 40℃ until the solvent evaporates. Add pre-hydrolyzed methyl orthosilicate (7.304g of methyl orthosilicate and 3.456g of water are stirred at 25℃ until clear), stir for 20min, then add a mixture of water and methanol with a volume percentage of 3%, stir evenly and centrifuge, repeat once, then wash thoroughly with ethanol and dry to obtain catalyst J.
[0120] Examples 58-75
[0121] In an intermittent reactor, 100 mmol of PO, 0.1 mmol of nanocage catalyst H or I or J containing active centers, and CO2 were introduced to a pressure of 1 MPa. The reaction time was 10 h and the temperature was 100°C. The recyclability of catalyst H or I or J was investigated, as shown in Table 4.
[0122] Table 4 The yield of cyclic carbonate obtained during the recycling of catalyst HJ / %
[0123]
[0124] According to Tables 1-4, the catalyst of the present invention is used for the cycloaddition of CO2 and epoxide to prepare cyclic carbonate, and has high activity and good recyclability. The yield of the cyclic carbonate obtained by the first catalysis can be as high as ≥99%, and the yield of the cyclic carbonate obtained by recycling 5 times is ≥98%.
[0125] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A cycloaddition catalyst, characterized in that The catalyst contains: Nanocage material CS, active center M(Salen)X 1 X 2 and the co-active center ZR*4Y; Among them, the active center M(Salen)X 1 X 2 In the formula, M is a metal ion, Salen is a Shiff base derivative, and X 1 , X 2 is an axial anion; depending on the valence state of the M metal, it may optionally contain X 1 and / or X 2 ; Among them, in the co-active center ZR*4Y, Z is nitrogen and / or phosphorus, R* is an aliphatic or aromatic carbon chain, and Y is a halogen anion; Wherein, the nanocage material CS is a mesoporous silica-based material containing carbon deposits and having a nanocage structure; The active center M(Salen)X 1 X 2 , having a structure shown in the following formula (I): Wherein: the structure in formula (I) One or more selected from the following structures: R 1 , R 2 At least one selected from tert-butyl, methoxy, H, nitro, phenyl, Cl, Br; M is a tetravalent metal Sn, or a trivalent metal Al, Co, Mn, Ru or Ir, or a divalent metal Zn, Sn, Cu or Co; When M is tetravalent metal Sn, X 1 , X 2 Selected from Cl - ,Br - , I - ,OAc - , OTs - , OTf - , NO3 - , ClO4 - , Cl3CCO2 - , F3CCO2 - , BF4 - , PF6 - , at least one of p-NO2-C6H4CO2; When M is a trivalent metal such as Al, Co, Mn, Ru or Ir, the active center M(Salen)X 1 X 2 Medium X 1 and X 2 Only one is kept, selected from Cl - ,Br - , I - ,OAc - , OTs - , OTf - , NO3 - , ClO4 - , Cl3CCO2 - , F3CCO2 - , BF4 - , PF6 - , at least one of p-NO2-C6H4CO2; When M is a divalent metal Zn, Sn, Cu or Co, there is no X 1 and X 2 .
2. The catalyst according to claim 1, wherein The carbon deposit content is 0.5-5.5 wt % based on the total weight of the nanocage material CS; and / or The mesoporous silica-based material is selected from one or more of SBA-6, SBA-16, FDU-1, FDU-12, KIT-5 and AMS-8; and / or The nano cage material CS is obtained by a sol-gel method combined with an inert atmosphere heat treatment.
3. The catalyst according to claim 1 or 2, wherein The preparation method of the nano cage material CS comprises: obtaining a solid mesoporous silica-based material containing a surfactant according to a sol-gel method, and heat treating the solid mesoporous silica-based material in an inert atmosphere, or first in an inert atmosphere and then in an oxygen-containing atmosphere.
4. The catalyst according to claim 3, wherein Heat treatment conditions include: The temperature is 300-1000°C; and / or The duration is more than 0.5 hours; and / or The inert atmosphere is a nitrogen and / or helium atmosphere; and / or The oxygen-containing atmosphere is an air atmosphere.
5. The catalyst according to claim 4, wherein Heat treatment conditions include: A temperature of 400-700°C; and / or The time is 2-6h.
6. The catalyst according to claim 3, wherein Heat treatment conditions include: Inert atmosphere: 300-500℃ for 0.5-4h; in air atmosphere: 500-700℃ for 1-6h.
7. The catalyst according to claim 1 or 2, wherein The mass of the nanocage material CS is related to the active center M(Salen)X 1 X 2 The ratio of the total mass of the co-active center ZR*4Y is (10-100): 1; and / or Active center M(Salen)X 1 X 2 The molar ratio of the co-active center ZR*4Y is 1:(0.5-3); and / or In the co-active center ZR*4Y, R* is a butyl group or a phenyl group.
8. The catalyst according to claim 1 or 2, wherein The mass of the nanocage material CS is related to the active center M(Salen)X 1 X 2 The ratio of the total mass of the co-active center ZR*4Y is (10-25):1; and / or Active center M(Salen)X 1 X 2 The molar ratio of the substance to the co-active center ZR*4Y is 1:(0.5-2).
9. The catalyst according to claim 1 or 2, wherein R 1 , R 2 At least one selected from tert-butyl, H.
10. The catalyst according to claim 1, wherein When M is tetravalent metal Sn, X 1 , X 2 Selected from Cl - ,OAc - , OTs - , Cl3CCO2 - , F3CCO2 - At least one of; When M is a trivalent metal such as Al, Co, Mn, Ru or Ir, the active center M(Salen)X 1 X 2 Medium X 1 and X 2 Only one is kept, selected from Cl - ,OAc - , OTs - , Cl3CCO2 - , F3CCO2 - At least one of; When M is a divalent metal Zn, Sn, Cu or Co, there is no X 1 and X 2 .
11. The catalyst according to claim 1 or 2, wherein The active center M(Salen)X 1 X 2 One or more selected from Co(N,N′-disalicylidene-1,2-cyclohexanediamine)OAc, Co(N,N′-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediamine)OTs, Co(N,N′-disalicylidene-1,2-cyclohexanediamine)Cl3CCO2, Sn(N,N′-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediamine)Cl2, Zn(N,N′-disalicylidene-1,2-cyclohexanediamine), Al(N,N′-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediamine)Cl.
12. The catalyst according to claim 1 or 2, wherein The co-active center ZR*4Y is selected from one or more of tetraphenylphosphonium bromide, tetrabutylammonium chloride and tetrabutylammonium bromide.
13. The method for preparing the catalyst according to any one of claims 1 to 12, wherein: The method comprises: 1 X 2 , the co-active center ZR*4Y, and the nanocage material CS are contacted with a solvent, and the solvent is removed; an encapsulation agent is added for encapsulation; then the mixture of water and alcohol is treated, and then washed with alcohol, and then dried.
14. The preparation method according to claim 13, wherein: The contact conditions include: dynamic mixing at room temperature for 0.5-5h; The solvent comprises ethanol and / or methanol; and / or The removal solvent temperature is -96°C to 61°C; and / or In the mixture of water and alcohol, the alcohol is selected from ethanol and / or methanol; and / or In the mixture of water and alcohol, the volume percentage of water is 1% to 50%; and / or The alcohol used for washing includes ethanol and / or methanol.
15. The preparation method according to claim 14, wherein: The solvent removal temperature is 20-40°C; and / or In the mixed solution of water and alcohol, the volume percentage of water is 2% to 25%.
16. The preparation method according to claim 15, wherein: In the mixed solution of water and alcohol, the volume percentage of water is 3% to 7%.
17. The preparation method according to any one of claims 13 to 16, wherein: The encapsulation agent is a silane coupling agent.
18. The preparation method according to claim 17, wherein: The silane coupling agent is one or more of methyl orthosilicate, propyltrimethoxysilane, hexamethyldisilazane and chlorotrimethylsilane.
19. Use of the cycloaddition catalyst according to any one of claims 1 to 12 in the preparation of cyclic carbonates by cycloaddition of CO2 and epoxide.
20. A method for preparing cyclic carbonate by cycloaddition of CO2 and epoxide, characterized in that: The method comprises contacting epoxide with CO2 in the presence of a cycloaddition catalyst, wherein the cycloaddition catalyst is the catalyst described in any one of claims 1 to 12, and the contact conditions include: a pressure of 0.5-5 MPa, a temperature of 20-120° C., and a time of 2-24 hours.
Citation Information
Patent Citations
Solid catalyst for hydration of epoxy compound to prepare diol and its application
CN102688776A
Catalyst for preparing diol by hydrating alkylene oxide, preparation method and uses thereof
CN110773232A